Job Loss : Bridging the Research and Policy Discussion - Lisa M. Lynch (Institute for the Study of Labor (IZA), 2005)
In this paper I discuss a structural problem facing the United States with respect to our policy responses in the context of trade and technological change and their impact on workers. Both trade and technological change have put enormous pressure on the U.S. economy to raise the skill level of the workforce. But the supply of skilled workers in the U.S. is just not keeping pace with the changes in demand due to technology and trade. Fixing this crisis requires us to understand both the skill quality of workers entering into the labor market and the nature of the stock of skills of workers already in the job market. This paper summarizes our knowledge on where workers get skills training and the returns to this training – both private and public. It then discusses how the academic research has informed the policy process and provides some suggestions on how academic economists can get involved in the policy debate to influence the direction of policy.
Keywords: J2; 330; human capital; Humankapital; Berufsbildung; Ungelernte Arbeitskräfte; Globalisierung; Technischer Fortschritt; Arbeitslosigkeit; Berufsbildungspolitik; Wirtschaftspolitische Beratung; Vereinigte Staaten